How do the year’s seasons and specific weather indices affect physical activity and the patterns of use of public open spaces in the Brazilian context? - Rech C.R. (2023)
© 2023, BioMed Central Ltd., part of Springer Nature.Background: Public open spaces (POS) can offer various resources to promote visitation and engagement in moderate-to-vigorous physical activity (MVPA). However, the influence of seasonal variations and specific meteorological conditions on this relationship remains unclear. Thus, this study aims to investigate the effect of seasonal variations and specific meteorological elements on different days of the week and times of day on POS use and POS-based MVPA in the Brazilian context. Methods: In 2018, repeated measurements carried out in Southern Brazil used a systematic observation to identify the presence of users in the POS and their engagement in MVPA. The meteorological elements (temperature, thermal sensation, and relative humidity), as well as seasonality (summer, autumn, winter, and spring), were aggregated into the observations. Results: A total of 19,712 systematic observations were conducted across nine POS. During these observations, a total of 59,354 users were identified. Out of theses, 39,153 (66.0%) were engaged in POS-based MVPA. The presence of users was found to be more frequent during the spring season (38.7%) and on weekends (ranging from 37.6 to 50.1% across seasons). Additionally, user presence was higher in the late afternoon (ranging from 36.4 to 58.2% across seasons) and at higher temperatures with lower relative humidity (p-value < 0.001). Regarding POS-based MVPA, it was more frequent during the winter season (36.4%) and on weekdays (ranging from 73.2 to 79.9% across seasons). Similarly, MVPA was higher in the late afternoon (ranging from 58.3 to 67.5% across seasons) and at lower temperatures and thermal sensations (p-value < 0.005). Conclusions: Higher presence of users in POS, as well as their visiting, to practice POS-based MVPA, depending on the seasons and specific meteorological elements. By creating infrastructure and conducive conditions, cities can encourage individuals to adopt more active and healthy behaviors. These findings emphasize the importance of designing urban spaces that promote physical activity and contribute to overall well-being.